The Mysterious Barricades : Language and its Limits - Berthoff, Ann E. (Book collections on Project MUSE., 1999)
"The Mysterious Barricades makes the case that escaping the enthrallment of recent theory in literary criticism and the philosophy of language will be impossible so long as the meaning relationship is conceived in dyadic terms. Ann E. Berthoff examines certain "dyadic misunderstandings," including the "gangster theories" fostered by Deconstruction and its successors, and offers "triadic remedies," which are all informed by a Peircean understanding of interpretation as the logical condition of signification."--Jacket.